ANALISIS UMUR PAKAI (LIFETIME) BEARING 6207 KNCG PADA KOMPONEN TAKE OFF ROLL MESIN TEXTURIZING MURATA 33-H DI PT. XYZ - Noviandani, Pradika; Thomas, Fendy; Zakaria, Kiki; Hadiaty Yuningsih, Siti (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
The textile industry plays an important role in the national economy, especially in absorbing labor and contributing to foreign exchange through export activities. One of the crucial processes in the textile production chain is yarn texturization, which greatly determines the physical and aesthetic characteristics of the yarn as the final product. PT. XYZ is a textile company that produces polyester-based textured yarn using a Murata 33-H type texturizing machine. This machine operates continuously at high speed and is highly dependent on the reliability of its mechanical components, one of which is the 6207 KNCG type bearing installed on the Take Off Roll section. Bearings function to support rotating shafts with high loads and speeds, so they are very susceptible to wear. Bearing failure can cause production downtime, damage to other components, and decreased product quality. Therefore, a predictive approach is needed in maintenance by analyzing the bearing lifetime theoretically. This study aims to calculate the estimated bearing lifetime and prepare a replacement schedule and appropriate preventive inspection to support smooth operations. The analysis results show that the theoretical lifetime of the 6207 KNCG bearing reaches 4.354,1 hours or around 181.6 operational days. Considering the safety factor, a replacement schedule of every 3.487,2 hours is recommended. In addition, routine inspections are carried out periodically to detect early signs of damage. This strategy is expected to improve machine reliability, maintenance cost efficiency, and production continuity at PT. XYZ.